Writing in another's voice: Frederick Kohner, Gidget and the father-daughter dynamic. Issue 4 (2nd October 2021) - Krauth, Nigel
ABSTRACT: As creative writers we produce dialogue between others, first-person narratives representing others, and in various ways the voices of characters not ourselves. Problems can arise when we feign other-culture, other-gender, other-era or other-aged voices. In this context, the case of Frederick Kohner and his character Gidget, based on his daughter Kathy, provides insights. This article suggests that the older-generation spin, the male slant, and the European culture perspective which Kohner massaged into the teenage voice of his Gidget books (1957–1968) was precisely why they were successful both commercially and as teenage literature in the 1950s and 60s. Kohner nuanced his daughter Kathy's voice so that it spoke to her peers as well as to a larger world. Occasionally in the argument I reference my own involvement in writing novels from the perspective of a teenager.